Self-supported PPy-encapsulated CoS2 nanosheets anchored on the TiO2−x nanorod array support by Ti–S bonds for ultra-long life hybrid Mg2+/Li+ batteries. Issue 43 (26th October 2020) - Liu, Chao; Zhao, Guangyu; Zhang, Li; Lyu, Pengbo; Yu, Xianbo; Huang, Huihuang; Maurin, Guillaume; Sun, Kening; Zhang, Naiqing
Abstract : PPy-encapsulated CoS2 nanosheets anchored on the TiO2− x nanorod array support by Ti–S bonds for ultra-long life hybrid Mg 2+ /Li + batteries. Abstract : Hybrid Mg 2+ /Li + batteries (MLIBs) are attractive energy storage devices that combine the advantages of Mg- and Li-rechargeable batteries. Recently, conversion-type transition metal sulfides (CTMS) have received growing attention as MLIB cathodes due to their large theoretical capacity, but these cathodes experience huge volumetric changes and dissolution of polysulfide intermediates during cycling, which cause the exfoliation of active materials and the deterioration of lifespan. Herein, self-supported PPy-encapsulated CoS2 nanosheets anchored on the TiO2− x nanorod array support by Ti–S bonds (TiO2− x @CoS2 @PPy) were prepared for the MLIB cathode. The Ti–S bonds and TiO2− x support effectively suppress the exfoliation of active material CoS2 and dissolution of polysulfide intermediates, leading to remarkable stability of the electrode during long cycles. Theoretical calculations demonstrate that TiO2− x possesses stronger chemical interaction with polysulfide intermediates, CoS2 and corresponding discharge products than pristine TiO2 . Additionally, the nanorod array structure and the outer PPy coating layer can provide a superior conductive network, buffer volumetric changes, and further prevent the APC electrolyte from reacting with polysulfide intermediates upon cycling. Therefore, the prepared electrodes exhibit impressive cycle stability (81.1% capacity retention at 5 A g −1 after 5000 cycles), high specific capacity (720.4 mA h g −1 ), superior energy density (416.5 W h kg −1 ), and good rate capability.